Characteristics of RNA degradation in the erythroid cell - Burka, Edward R. (1969)
The characteristics of ribonucleic acid (RNA) degradation in intact reticulocytes have been investigated. The rate of degradation during in vitro maturation at 37°C is approximately 4% per hr. RNA degradation does not proceed at 0°C, and the rate of degradation is temperature dependent with an optimum at 50°C. The process is not dependent upon glycolysis. Although all types of RNA progressively decrease during in vivo maturation, ribosomes are degraded at a rate greater than that of soluble RNA. RNA within the cell fluxes freely back and forth between the free and membrane-bound forms. The rate of loss of RNA in the membrane-bound compartment, both in the intact cell and in isolated membranes, is approximately threefold that found in the cell as a whole. During maturation the proportion of total cell RNA which is bound to the membrane decreases. The bulk of RNA destroyed is derived from the free compartment, but bound is also destroyed. The cell membrane participates in RNA metabolism and may be a site of RNA degradation in the erythroid cell.